Analisis Peran Aktor Dalam Implementasi Sistem Akuntansi Paroki Di Keuskupan Agung Semarang - Devin Nathaniel Purwandi Soelistijo (Jurnal Akuntansi Bisnis, 2023)
Analisis Peran Aktor Dalam Implementasi Sistem Akuntansi Paroki Di Keuskupan Agung Semarang Devin Nathaniel Purwandi SoelistijoProgram Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Katolik SoegijapranataCorresponding author email: devinnath49@gmail.comAbstractThe church is a non-profit organization that is involved in various activities related to the spiritual life of the people. Church involvement in various activities requires the church to have a reliable accounting system to increase church accountability. The parish is a community of Catholics with a mission to strengthen the church and support the community. The existence of an accounting system is needed to ensure the goals of the parish are met. The purpose of this study is to understand the dynamics that occur in parishes when planning to implement an accounting system. The case study method based on institutional work theory is applied to explain the dynamics of the process of implementing the accounting system in the Archdiocese of Semarang. The analysis shows that the process of implementing the accounting system is a disruptive work process, especially when the actor (KAS accounting team) tries to change the mindset of the parish.